Clinical Significance of Hepatitis B Virus Precore and Core Promoter Variants in Korean Patients With Chronic Hepatitis B. Issue 1 (January 2015) - Yim, Sun Young; Um, Soon Ho; Young Jung, Jin; Kim, Tae Hyung; Kim, Jin Dong; Keum, Bora; Seo, Yeon Seok; Yim, Hyung Joon; Jeen, Yoon Tae; Lee, Hong Sik; Chun, Hoon Jai; Kim, Chang Duck; et al.
<x xml:space="preserve">Abstract</x> Background/Aim: We aimed to clarify the clinical significance of precore (preC)/core promoter (CP) variants of hepatitis B virus (HBV) in chronic hepatitis B (CHB) patients. Methods: We assessed serum HBeAg, HBV DNA levels, alanine transferase (ALT) levels, and progression of liver fibrosis in 226 Korean CHB patients, presumed to be infected with genotype C HBV, to analyze HBV variants in the preC region (G1896A) and CP regions (A1762T, G1764A). Results: CP and preC variants were more frequently found in HBeAg-negative patients than in HBeAg-positive patients (P<0.05). HBeAg-positive patients with CP variants had higher ALT levels and more advanced fibrosis scores (all P<0.01) than those without variants; those with preC variant had lower HBV DNA levels (P=0.009), with no significant difference in ALT levels and fibrosis scores. However, no significant correlation was found between HBV variants and clinicopathologic findings in HBeAg-negative patients. Furthermore, multivariate analysis revealed that (1) progression of liver fibrosis (≥F2) was associated with older age in both HBeAg-positive and HBeAg-negative patients (P<0.05) and with CP variants in the HBeAg-positive group (P=0.007), and (2) HBV DNA levels were positively correlated with ALT levels, irrespective of HBeAg (P<0.05), whereas they were negatively correlated with the presence of preC variant in the HBeAg-positive group (P=0.004). Conclusions: In HBeAg-positive CHB patients infected with genotype C HBV, preC variant was associated with enhanced host immune response with lower HBV DNA levels, whereas CP variants were associated with severe liver damage and liver fibrosis progression.